Panduan Berbasis Person-Centered Guru Untuk Mendukung Kesejahteraan Psikososial Siswa: Pengembangan Dan Kelayakan Platform Bimbingan Digital - Ate Nurhayati; Bakhrudin All Habsy; Mochamad Nursalim (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
Limited access to formal school mental health services has increased the importance of subject teachers as providers of initial psychosocial support. However, practical guidance that helps non-counselor teachers apply person-centered principles in everyday classroom interactions remains scarce. This study aimed to develop and establish the preliminary feasibility and content validity of a digital person-centered support guide for junior high school subject teachers. The study employed the ADDIE model within an early-stage feasibility framework. A needs analysis was conducted in four junior high schools in South Halmahera, Indonesia. The product was developed as a Google Sites platform, validated by two experts, and pilot-tested with four subject teachers. The findings showed that all validation items were rated as relevant (I-CVI = 1.00; S-CVI/Ave = 1.00), although several linguistic and technical aspects still required refinement. Teachers also reported high initial acceptability and perceived usefulness. These findings suggest that the guide has potential as a school-based psychosocial support resource, although broader field testing is still needed.